Developing Entrepreneurial Mindsets in Agricultural Education: A Review Study - Hayatul Khairul Rahmat; Rezki Putra; Nur Asma Deli; Tri Kurniaty; Rizqi Qurnia Zary; Nur Hidayatul Hafidzah (PT Hakhara Akademia Indonesia, 2025)
The increasing complexity of global agri-food systems, driven by technological innovation, climate change, and market globalization, has intensified the need for entrepreneurial competencies among agricultural graduates. Agricultural education institutions are therefore expected not only to transmit technical knowledge but also to cultivate entrepreneurial mindsets that enable graduates to identify opportunities, manage uncertainty, and create sustainable value. This review study synthesizes international literature on the development of entrepreneurial mindsets within agricultural education, focusing on conceptual foundations, pedagogical approaches, and structural challenges. Drawing on peer-reviewed studies from entrepreneurship education, agricultural education, and rural development, the review identifies experiential learning, problem-based instruction, and industry engagement as key mechanisms for fostering entrepreneurial orientation. However, persistent barriers such as curriculum rigidity, limited educator capacity, and weak institutional linkages constrain effective implementation. The study argues that embedding entrepreneurship in agricultural education requires systemic transformation rather than isolated curricular interventions.